Analysis of the Influence of Perception of Usability, Perception of Convenience, and Security of Online Shopping on Purchase Decisions on the Shopee Marketplace - Nabilah Nur Aini Putri; Titin Titin; Abid Muhtarom (Sean Institute, 2024)
This study aims to analyze the influence of the perception of usability, perception of convenience, and security of online shopping on purchase decisions on the Shopee marketplace. The study used an associative quantitative approach with the object of housewives and adolescents RT 01/RW 02 Tlogoanyar who had used Shopee. The research sample amounted to 81 respondents determined by purposive sampling technique. Data were collected through a Likert scale questionnaire and analyzed using SPSS version 25 through validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, partial tests, simultaneous tests, determination coefficients, and dominant tests. The results showed that the perception of usability had a positive and significant effect on purchase decisions, while the perception of ease and security of online shopping had a positive but not partially significant effect. Simultaneously, the three independent variables have a positive and significant effect on purchasing decisions. The R-Square value of 0.332 indicates that 33.2% of the variation in purchasing decisions can be explained by the perception of usability, the perception of convenience, and the security of online shopping, while 66.8% is explained by other variables outside the study. The most dominant variable is usability perception.